Technology Transfer In Indonesia And China: A Comparative Study - Abdul Thalib (Jurnal Hukum IUS QUIA IUSTUM, 2016)
The problems in this study: first, whether the patent system in Indonesia and China is effective for technology transfer? Second, what are the roles of the Chinese and Indonesia government for technology transfer? This study uses a normative legal research. The results of the research concluded that first, there are no special regulations in Indonesia regulating the transfer of technology. Some policies are contradict to each other and are directed to meet the needs of special parts of industry. While in China, the rules governing the transfer of technology experiences some changes along with China's accession to WTO. Second, the Indonesian government has attempted to use some performance requirements in the regulation of foreign investment for the faster transfer effect from technology. However, the existing legislation is weak or not enforced, and there are no special incentives to encourage FDI to upgrade local technological capabilities.